Disempowerment through the Backdoor: The Impact of Populist Parties on the National Parliament in Poland. Issue 4 (3rd March 2021) - Maatsch, Aleksandra
Abstract: Do populist governments disempower parliaments? If so, which strategies do they employ to do it? The empirical analysis here concerns two legislative periods in Poland: T1 2011–2015 (centre-right coalition, populist actors in the opposition) and T2 2015–2018 (populist government). The article traces changes in formal rules regulating scrutiny and law-making but also how these rules were interpreted and exercised. The article addresses the following explanatory factors: position in government, strength of parliamentary formal provisions and the readiness of political actors to revise institutional competences. The article shows that although changes to formal parliamentary powers were minor, disempowerment of the legislative was profound. The outcome has actually been achieved through radical changes in parliamentary practices regarding both law-making and scrutiny.